2015
DOI: 10.1080/2162402x.2015.1008805
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of miR-mediated HLA-G regulation and the associated immune cell infiltration in renal cell carcinoma

Abstract: In human tumors of distinct origin including renal cell carcinoma (RCC), the non-classical human leukocyte antigen G (HLA-G) is frequently expressed, thereby inhibiting the cytotoxic activity of T and natural killer (NK) cells. Recent studies demonstrated a strong post-transcriptional gene regulation of the HLA-G by miR-152, -148A, -148B and -133A. Standard methods were applied to characterize the expression and function of HLA-G, HLA-G-regulatory microRNAs (miRs) and the immune cell infiltration in 453 RCC le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 56 publications
0
94
0
Order By: Relevance
“…The entire study has been approved by the local Ethical Committee at the University of Erlangen-Nürnberg and specimens were collected in accordance with the World Medical Association Declaration of Helsinki. Details on tissue microarray (TMA) composition and tumour characteristics have been published previously55. In short, archival FFPE tissues were reclassified according to the 2004 World Health Organization classification of renal tumours and the 2002 tumour node metastasis (TNM) classification by two uropathologists.…”
Section: Methodsmentioning
confidence: 99%
“…The entire study has been approved by the local Ethical Committee at the University of Erlangen-Nürnberg and specimens were collected in accordance with the World Medical Association Declaration of Helsinki. Details on tissue microarray (TMA) composition and tumour characteristics have been published previously55. In short, archival FFPE tissues were reclassified according to the 2004 World Health Organization classification of renal tumours and the 2002 tumour node metastasis (TNM) classification by two uropathologists.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Multiple mechanisms have been implicated in tTreg development and suppressive function, including more recently miRNA's effects on posttranscriptional gene regulation. [15][16][17][18] The miR-146 family includes 2 main members, miR-146a and miR-146b, which are both highly expressed and play important roles in cell proliferation and function in diverse cell types, including T and B cells. Studies of breast cancer cells have shown a Foxp3-dependant increase in the expression of miR-146b and, to a lesser extent, miR-146a, 19 which results in reduced breast cancer cell proliferation and enhanced apoptosis via negative regulation of nuclear factor kB (NF-kB).…”
Section: Cd25mentioning
confidence: 99%
“…Total RNA was extracted from cell pellets employing TRIzol Reagent (Thermo Fisher Scientific), digested with DNase I (Promega, Mannheim, Germany) and applied for cDNA synthesis utilizing the RevertAidTM H Minus First Strand cDNA synthesis kit (Thermo Fisher Scientific) as recently described [23]. …”
Section: Methodsmentioning
confidence: 99%